MANAJEMEN GURU PENDIDIKAN AGAMA ISLAM YANG BERORIENTASI DALAM PEMBELAJARAN AKTIF PADA MI TAHFIDZ ANWAHA - M. Husin; M. Raihan Saputra, M. Riyan Fakhrian Noor, Syahrani (CV. ADIBA ASIHA AMIRA, 2023)
Active learning is a form of learning that allows interactions between teachers and students to develop optimally. The aim of this research is to determine differences in student learning outcomes, determine teachers' abilities in managing learning, and determine student responses to active learning. This research uses a data collection design and questionnaire in the form of frequency distribution in an effort to implement active learning. This research focused on classes IV, V and class VI, totaling 50 people at MI Tahfidz Anwaha. The research results show that there are significant differences with previous student learning outcomes. The application of active learning strategies, interactive methods, and creative media varies according to the teacher's ability to create media, the teacher's ability to manage learning well, and positive student responses.